Human Values and Work Engagement: The Mediating Role of Authenticity Among Workers in a Spanish Religious Organization - Ortiz-Gómez, Mar; Ariza-Montes, Antonio; Molina-Sánchez, Horacio (Frontiers in Psychology, 2020)
Nowadays religious organizations play a leading role in the third sector, contributing to maintaining the welfare state in a large number of countries in sectors such as health, education or social services, among others. These organizations provide a service to their users, aiming to transmit the predominant values in their mission statement and simultaneously promote both authenticity and work engagement in their employees. Indeed, the purpose of this article is to evaluate the link between human values and work engagement, as well as the mediating role of authenticity in this relationship. To this end, 938 workers of a Catholic religious organization, which constitutes a relatively unexplored context, is employed. To test the research model and hypotheses, this investigation uses PLS (Partial Least Squares). It covers two notable research gaps. First, the results confirm the direct links between human values, authenticity and work engagement within the context of religious organizations. Second, they provide evidence of the mediating role exercised by authenticity in the relationship between human values and work engagement.